Communication experiences of Pekanbaru city patients receiving In Vitro Fertilisation (IVF) treatment in Malaysia fertility clinics - Rumyeni; Susanne Dida; Hadisiwi, Purwanti; Yanti Setianti (Penerbit Universiti Kebangsaan Malaysia, 2021)
Doctor-patient communication is important in all medical consultations including for In Vitro Fertilisation (IVF) treatment. An unfavourable communication experience can cause a patient to stop taking the treatment, move to another local fertility clinic, or even seek treatment abroad. There are still few studies documenting communication experiences of patients with infertility seeking reproductive treatment in other countries. This study aimed to describe the communication experiences of Indonesian IVF patients receiving IVF treatment from medical practitioners in fertility clinics in Malaysia. This study used Benner's interpretive phenomenology framework in its approach and when analysing the results. Data collection was carried out using in-depth and semi-structured interviews with 11 IVF patients from Pekanbaru city Indonesia who received IVF treatment in fertility clinics in Malaysia. This study found three main themes shared by the IVF patients’ communication experiences: 1) memorable experiences (friendliness and caring, empathy, honesty and openness, clarity and adequacy of the information, and easiness of communication; 2) less memorable experiences (less interpersonal communication, less warm non-verbal communication, and miscommunication); and 3) communication barriers (English). These findings have important implications for both the prospective patients receiving cross-border fertility treatment in the future and for service providers providing fertility treatment to improve doctor-patient communication.